Dynamic Stiffness and Damping Characteristics of a Shaft Damping Ring: A Combined Hyperelastic and Viscoelastic Constitutive Model - Miaomiao Li; Jian Chen; Rupeng Zhu; Cheng Duan; Shuai Wang; Xiong Lu (Shock and Vibration)
At higher velocities, the helicopter tail transmission system encounters notable difficulties due to excessive bending vibrations. The shaft damping ring installed on the shaft system was shown to effectively suppress the shaft system vibrations. In this paper, the dynamic stiffness and damping characteristics of polyurethane shaft damping rings were studied using hyperelastic and viscoelastic constitutive models. The constitutive model and the damping ring material parameters were determined using uniaxial tensile and double-shear frequency scanning tests. Based on the test results, the dynamic damping ring characteristics were simulated and verified by dynamic stiffness tests; the influence of structural parameters and operating conditions on the dynamic stiffness and damping characteristics of the damping ring were obtained. The results provide a theoretical basis for the design of shaft systems with reduced sensitivity to vibrations.